Analiza tehnološkega, procesnega in organizacijskega vidika vpeljave sistema za upravljanje konfiguracije - Polančič, Gregor (Uporabna informatika (Ljubljana), 2009)
The paper summarizes the implementation of the project of the establishment of web services introduced to Slovenia for the first time with the intention to make access to mutual funds by using qualified digital certificates. Nowadays the framework of information science operation in society is by all means defined also by its ability of creating added value in the spirit of increasing competitiveness of products and services that are available to customers and the competitiveness of a company as a whole. The development of e-business operations with the offer of financial services is to a great extent directed also by changes of legislation and valid regulations. Opportunities to modernize and improve the quality of implementing inner processes of a company may also be hidden in designing new services and in aspirations to be a step before competitors. Is it possible to turn the power of the paradigm shift to our advantage and to speed up natural processes in implementing changes in business operations?
Keywords: razvoj programske opreme; upravljanje; management; upravljanje konfiguracije